Analysis of a Mechanical Solver for Linear Systems of Equations (Journal of Computational Mathematics, 2001)
In this contribution we analyse some fundamental features of an iterative method to solve systems of linear equations, following the approach introduced in a previous work [1]. Such questions range from optimal parameters and initial conditions to comparison with other methods. An interesting result is that a priori we can give an estimation of the number of iterations to get a given accuracy.
Keywords: Iterative method; Linear systems; Classical dynamics.